Hook - Davis Halifax, Nancy Viva, 1956- (Hugh MacLennan poetry series., 2015)
See her? / Steadfast and firm her / branches graze the mantle of quiet clouds / as she elaborates her claim Haunted by indifference toward systemic violences and the disregard endured by those people labelled as "problems," nancy viva davis halifax's poems articulate the constraints of discredited lives. Conveying her experiences witnessing homelessness, poverty, disability, and chronic illness on the streets and within women's emergency shelters, davis halifax orients readers to recognize ongoing suffering in our society. One poem, a purl of four words, reminds the reader that language entangles and unbinds lives, and that life is an unfastening, a knitting by which some are lost and others made separable. These are unregulated poems, poems that refuse indifference and reassert mutuality. They are not an argument, they are not assured, not facts, not a problem, not a resource, but an opening.